2023
DOI: 10.3389/fcimb.2022.1068000
|View full text |Cite
|
Sign up to set email alerts
|

Tenacibaculosis caused by Tenacibaculum maritimum: Updated knowledge of this marine bacterial fish pathogen

Abstract: Tenacibaculosis occurs due to the marine bacterial pathogen Tenacibaculum maritimum. This ulcerative disease causes high mortalities for various marine fish species worldwide. Several external clinical signs can arise, including mouth erosion, epidermal ulcers, fin necrosis, and tail rot. Research in the last 15 years has advanced knowledge on the traits and pathogenesis mechanisms of T. maritimum. Consequently, significant progress has been made in defining the complex host-pathogen relationship. Nevertheless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 139 publications
(175 reference statements)
1
20
0
Order By: Relevance
“…The pathogenesis and epidemiology of T. maritimum is far from being a resolved issue. However, challenge studies have found high mortality (>90%) for Atlantic salmon exposed to high concentration T. maritimum – 2.7 × 10 7 cfu/mL (Nowlan et al., 2021), and other studies have shed light into the multifactorial nature of the disease and interaction with other bacteria (Wynne et al., 2020) leading to calls for further studies on T. maritimum pathogenesis (Mabrok et al., 2022). Furthermore, we propose that case–control epidemiological studies are needed in order to understand the risk factors associated with mouth rot and exposure to T. maritimum before a conclusion is reached in regard to the value of vaccination against T. maritimum .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathogenesis and epidemiology of T. maritimum is far from being a resolved issue. However, challenge studies have found high mortality (>90%) for Atlantic salmon exposed to high concentration T. maritimum – 2.7 × 10 7 cfu/mL (Nowlan et al., 2021), and other studies have shed light into the multifactorial nature of the disease and interaction with other bacteria (Wynne et al., 2020) leading to calls for further studies on T. maritimum pathogenesis (Mabrok et al., 2022). Furthermore, we propose that case–control epidemiological studies are needed in order to understand the risk factors associated with mouth rot and exposure to T. maritimum before a conclusion is reached in regard to the value of vaccination against T. maritimum .…”
Section: Discussionmentioning
confidence: 99%
“…T. maritimum is a ubiquitous marine gram‐negative rod associated with generalized tenacibaculosis and mouthrot in Atlantic salmon (Frisch, Småge, Vallestad, et al., 2018). It is present in all salmon farming regions in the world, although it is not specific to salmonids (Avendaño‐Herrera et al., 2006; Mabrok et al., 2022). Fish affected with tenacibaculosis may display erosive and ulcerative lesions in mouth, skin and fins which can eventually lead to death, however, the pathogenicity of the infection remains unclear and it is yet to be elucidated (Avendaño‐Herrera et al., 2006; Mabrok et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results presented for enzymatic activity: 1 , prepared with artificial seawater; 2 , sterilized seawater and 3 , saline solution. 4 , indicates a positive result with all three-suspension media. nd, No data; w, weak reaction; v, variable.…”
Section: Genome Analysis Phylogeny and Featuresmentioning
confidence: 99%
“…Most Tenacibaculum species have been described from fish, marine sediments, macroalgae and invertebrates [1] and are considered non-pathogenic. Notwithstanding, nine members are associated with a disease termed tenacibaculosis, which causes ulcerative external infections in commercially farmed fish worldwide [2][3][4][5]. Fish affected by this disease present skin lesions (with injuries that are commonly ulcerative), frayed fins, tail rot, eroded mouth and haemorrhaging gills [2][3][4].…”
Section: Introductionmentioning
confidence: 99%